Malignant peripheral nerve sheath tumours in a patient with Neurofibromatosis-1 - Fatima Iqbal; Muhammad Jamaluddin; Fakiha Bukhari; Omama Subul Islam (Journal of the Pakistan Medical Association, 2023)
Malignant peripheral nerve sheath tumour (MPNST) is an uncommon type of soft tissue tumour which most commonly arises in the setting of Neurofibromatosis-1 (NF-1) or in the presence of another nerve sheath tumour. NF-1 is an autosomal dominant syndrome which is diagnosed based on clinical criteria. People suffering from NF-1 are at a higher risk of developing tumours, especially MPNST. MPNST can occur anywhere along the distribution of nerve roots but most commonly involves the limbs and trunk. The prognosis of MPNST in the setting of NF-1 is grave as the distant metastasis develops earlier than non-syndromic cases. Pre-operative diagnosis is difficult as there is no gold standard radiologic technique or characteristic radiological features. ---Continue